Vascular Silicone Injection of Fresh Cadaveric Cow Cranium: Alternative Training Model For The Human Brain - (:unkn) unknown (My University, 2015)
Arka plan: İnsan beyin damar sisteminin anatomik ve fizyolojik farklılıkları, arteriyel ve venöz sistemlerin silikon enjeksiyonu ile görülebilir. Yeni bir yöntem olarak, taze inek kranium kadavrasının silikon injeksiyonu, mikroanatomik çalışmalar için insan beyninin silikon enjeksiyonuna bir alternatiftir. Amaç: Amacımız, silikon enjeksiyon tekniği kullanarak taze inek kranium kadavrasının renkli silikon enjeksiyonu için geliştirilmiş bir metot bildirmektir. Yöntem: İnsan beynine alternatif olarak mikroanatomik diseksiyonlarda kullanmak üzere beş adet taze inek kraniumu, injekte edildi. Hazırlık, majör damarların yıkanması ve renkli silikon injeksiyonunu içerir. Sırasıyla internal karotis arter ve internal juguler venlerin kateterle kanülasyonu, ana arter ve venlerin su ile yıkanması, kraniumun alkol veya formaldehit ile fikse edilmesi, kırmızı ve mavi silikon ile arter ve venlerin renkli injeksiyonu uygulandı. Bulgular: Silikon injeksiyonları, taze inek kranium kadavrasında, küçük beyin damarlarının ve mezenkimal yapıların içine renkli solüsyonların derin penetrasyonunu sağladı. İnjeksiyon yapılmış beş kraniumun dördünde başarılı olundu. Birinde ise suboptimal sonuçlara varıldı. Sonuç: Mikroanatomik çalışmalar için kraniumun damarlarının anatomik ve fizyolojik değerlendirilmesi temelinde, silikon injekte edilmiş inek kranium kadavrası, insan beyin kadavrasına bir alternatif olarak önerilmiştir.

Background: Anatomical and physiological variations of the human brain's vascular system can be observed via silicone injection of the arterial and venous systems. As a novel method, the injection of a fresh cadaveric cow cranium with silicone is an alternative to using the human brain for microanatomical studies. Objective: To report on an improved method for the colored silicone injection of a fresh cadaveric cow cranium using a silicone injection technique. Methods: Five fresh cow crania were injected as an alternative to human brains for microanatomical dissection, in which the preparation consisted of the irrigation of the major vessels and the injection of colored silicone. Cannulation of the internal carotid arteries and the internal jugular veins with catheters was performed, and the vasculature was irrigated with water (major arteries and veins). The fixation of the specimen with either formaldehyde or alcohol, and the colored injection of the arteries and veins with red and blue silicone, respectively, was then performed. Results: The silicone injections resulted in the deeper penetration of the colored solutions into the small cerebral vessels and mesenchymal structures of the fresh cadaveric cow crania. Of the five injected specimens, four exhibited successful injections, while one had suboptimal results. Conclusion: Silicone injection of the cadaveric cow brain, based on the anatomical and physiological assessment of the vasculature of the specimen for microanatomical studies, is suggested as an alternative to using human brain specimens.
Taze İnek Kranium Kadavrasının Vasküler Silikon İnjeksiyonu: Eğitim Modeli Olarak İnsan Beynine Bir Alternatif
Keywords: Nörolojik Bilimler